A review of the pathway to reducing youth unemployment in Sub Saharan Africa through agriculture and agribusiness - Toritseju Begho; Tare Philip Daubry (Discover Global Society)
Abstract Youth unemployment remains a challenge in Sub-Saharan Africa. There are suggestions that agriculture, with the right interventions, holds the potential to serve as a transformative sector for creating sustainable and productive jobs. However, there is a need to synthesize findings from studies across multiple countries to draw actionable lessons. This review highlights the state of youth unemployment in Sub-Saharan Africa and synthesizes existing research on strategies to motivate youths to engage in agriculture. The review finds that while agriculture in the region offers significant opportunities, many young people still perceive farming as an undesirable career due to associations with poverty, hard labour and low economic returns. The review identifies several systemic issues including negative social and cultural perception of agriculture, limited access to land, inadequate training and resources, gender disparities in access to resources and decision-making, barriers to credit and modern farming equipment, lack of infrastructure, the digital divide between urban and rural youth and skills mismatches. Climate change was also identified as a key barrier. The paper identifies interventions, supportive policies and community-driven initiatives such as increasing awareness of agriculture as a viable business, reducing entry barriers through incorporating business-oriented agricultural education, coordinated efforts to reform land tenure, investment in rural infrastructure, providing targeted financial incentives and mentorship and using behavioural nudges like skill certification and training which can address these barriers and catalyse change. Consequently, agriculture can become a driving force for job creation, economic empowerment and contribute to the long-term solutions to youth unemployment in Sub-Saharan Africa.